Epidemiology and prevention of influenza in children in Argentina and Brazil - González Ayala, Silvia Elena (2017)
A group of influenza experts from Argentina and Brazil got together to discuss the burden of influenza in children, review current vaccine coverage rates in both countries, analyze vaccine effectiveness, and discuss strategies to improve prevention. Active surveillance of respiratory viruses is carried out nationwide in both countries. Years 2014 and 2015 were mild influenza seasons; influenza virus type A/H3N2 prevailed, whereas type B represented less than 30% of isolates. Trivalent inactivated influenza vaccine is included in National Immunization Programs for 1) children 6 months to 2 years old in Argentina; 2) children 6 months to 5 years old in Brazil; and 3) all high-risk individuals. Coverage rates in both countries were about 80% (albeit lower for the second dose). Experts from both countries proposed the following strategies to improve prevention: 1) increase surveillance; 2) assess effectiveness and long-term safety of influenza vaccines; 3) reinforce vaccination programs in order to increase coverage rates; and 4) consider introducing more effective vaccines, such as adjuvanted trivalent vaccines. In Argentina, estimating casefatality rates was also recommended. Other proposed actions included enhancing education of health professionals and the lay community, and better use of communication resources to raise awareness of the burden of influenza and promote vaccine uptake.